Validation of the Brazilian version of Questionnaire of Smoking Urges-Brief (Archives of Clinical Psychiatry, 2007)
BACKGROUND: The evaluation of craving is very important to treatment of tobacco dependence. OBJECTIVE:The objective of this research was to validate the Brazilian version of the Questionnaire of Smoking Urges-Brief (QSU-B). METHOD: Subjects enrolled to this experimental study were randomized into groups of zero, 30 and 60 minutes of tobacco abstinence. The study group was composed by 201 subjects (134 females and 67 males), age range: 18 to 65 (M = 38.15). The assessment instruments were, in addition to the QSU-B: Social and Demographical Data Form, Visual Analogic Scale for Craving, Fagerström Test for Nicotine Dependence and Anxiety and Depression Beck Inventories. RESULTS: The two-factor factorial analysis presented a total variation of 78.46% and the correlation between these factors was significant and of high intensity (r = 0.636; p < 0.001). All Cronbachs alpha values from QSU-B were above 0.70. We observed a correlation between the QSU-B total score and the Visual Analogic Scale (r = 0.656; p < 0.001), and also with Fagerströms question 1 (r = 0.201; p = 0.004) and question 2 (r = 0.257; p < 0.001). CONCLUSION: QSU-Bs Brazilian version proved to be an adequate psychometric instrument for the use both in research and in clinical settings.